LANGUAGE PERFORMANCE OF CONFLICT BY MAIN CHARACTER JAKE SULLY IN MOVIE AVATAR 2: THE WAY OF WATER - Putri Alfianti Arfah; Fatimah Hidayahni Amin; Abdullah (International Journal of Business English and Communication, 2024)
This research analyzed the language performance in the movie “Avatar 2: The Way of Water”. This study aims to find out what are the language performance that the main character namely Jake Sully used in the conflict situations that contains language forms and language functions. This study used qualitative method with a descriptive design that collected from the whole utterances of the conflict situations that the main character produced in the movie. Apart from that, it also aims to find out how the main character solves the problems that he faces. The result of this study, it found that there are two types of conflict: internal conflict and external conflict that contained in the movie. The language forms used in the conflict situations are words, phrases, and sentences. Meanwhile, the language functions used in the conflict situations are expressive, directive, referential, and poetic functions. Problem solving methods used by the main characters are avoidance, pacification, competition, compromise, and creative integration.